2016
DOI: 10.5487/tr.2016.32.2.149
|View full text |Cite
|
Sign up to set email alerts
|

A Probiotic Preparation Alleviates Atopic Dermatitis-Like Skin Lesions in Murine Models

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease with a complex etiology that encompasses immunologic responses. AD is frequently associated with elevated immunoglobulin (Ig) E levels, and common environmental factors contribute to its pathogenesis. Several recent studies have documented the role of specific lactic acid bacteria in the treatment and prevention of AD in humans and mice. In this study, the efficacy of Duolac ATP, a probiotic preparation, was determined in a mouse model with AD-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Recent studies have shown that certain probiotics can play a role in the treatment and prevention of AD ( Kim et al, 2012 , 2015 ). Duolac ATP possesses anti-inflammatory properties in a DNCB-induced AD mouse model ( Kim et al, 2016 ). However, the exact mechanism by which Duolac ATP regulates the immune system has not been well defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that certain probiotics can play a role in the treatment and prevention of AD ( Kim et al, 2012 , 2015 ). Duolac ATP possesses anti-inflammatory properties in a DNCB-induced AD mouse model ( Kim et al, 2016 ). However, the exact mechanism by which Duolac ATP regulates the immune system has not been well defined.…”
Section: Discussionmentioning
confidence: 99%
“…Duolac ATP is a probiotic preparation containing four probiotics strains: L. casei , L. plantarum , Lactobacillus rhamnosus , and B. lactis . Duolac ATP has been previously evaluated for anti-inflammatory activity in a trinitrobenzene sulfonic (TNBS)-induced colitis model ( Cha et al, 2014 ) and a 1-chloro-2,4-dinitrobenzene (DNCB)-induced AD model ( Kim et al, 2016 ). However, these studies focused on the therapeutic effects of Duolac ATP through fragmentary indicators.…”
Section: Introductionmentioning
confidence: 99%
“…SRTA00; R&D Systems, Inc.), and interferon-γ (IFNγ; cat no. SRIF00; R&D Systems, Inc.) were determined using ELISA kits (R&D Systems, Inc., Minneapolis, MN, USA), according to the manufacturer's recommendations ( 25 ). The level of prostaglandin E 2 (PGE 2 ) was also determined using an ELISA kit purchased from R&D Systems, according to the manufacturer's instructions ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…Optical density was measured at 540 nm using an enzyme-linked immunosorbent assay (ELISA) reader (Dynatech Laboratories, Chantilly, VA, USA) (Kwon et al, 2016[ 32 ]). Serum levels of prostaglandin E 2 (PGE 2 ) were determined according to the manufacturer's instructions (ELISA kit, R&D Systems, Minneapolis, MN, USA) (Kim et al, 2016[ 29 ]). The pro-inflammatory cytokines including IL-1β, IL-6 and TNF-α, and cartilage degeneration mediators such as cartilage oligomeric matrix protein (COMP) and C-telopeptide of type II collagen (CTX-II) were also determined using ELISA kits (R&D Systems, Minneapolis, MN, USA) according to the manufacturer's recommendations.…”
Section: Methodsmentioning
confidence: 99%